Improving Women's Skills And Economy In Kecupak II Village, Pakpak Bharat With Pandan Handicrafts Training - Lister Berutu; Nita Savitri; Nurbani, Nurbani (Sean Institute, 2024)
This study aims to explore the empowerment of pandan craftsmen as a means of improving the economic welfare of women in Kecupak II Village, PGGS District, Pakpak Bharat Regency. The pandan handicrafts in this village have significant potential for development, but limited access to markets and skill training has resulted in suboptimal income for artisans, especially women. Through a community empowerment approach, this research focuses on skill development, product quality enhancement, and broader market access. The research method used is a qualitative approach with data collection techniques including interviews, observations, and focus group discussions (FGD) with artisans, community leaders, and other relevant stakeholders. The findings indicate that training in skills, strengthening business management, and improved market access can increase product quality and competitiveness of pandan handicrafts in local and regional markets. Furthermore, this empowerment initiative has opened up economic opportunities for women, increased household incomes, and strengthened the role of women in the village economy. As a recommendation, further support from the government and related institutions is needed to provide advanced training, broader marketing access, and business capital assistance to sustain and advance the pandan handicraft industry. In this way, the empowerment of pandan craftsmen in Kecupak II Village is expected to become a model for community-based economic empowerment that empowers women and enhances the overall well-being of the village community.